PELATIHAN KETRAMPILAN PEMBUATAN PELEMBUT DAN PEWANGI PAKAIAN BAGI IBU - IBU PKK DI DESA KANGKUNG, KECAMATAN MRANGGEN, KABUPATEN DEMAK - Heny Kusuma Yanti; Vita Paramita; Rizka Amalia; Gina Novela; Igin Ebeniene Rhamvy (Sekolah Vokasi Universitas Diponegoro, 2019)
Community service training in the Kangkung village, Mranggen Subdistrict, Demak Regency was carried out by exposing the material, introducing tools and materials and their functions, how to work to make softeners and deodorizers. The division of participants into 3 groups, each group gets tools and materials for making softeners and deodorizers in the hope that cooperation can be established between group members and increase entrepreneurship, can improve skills, reduce expenses if the fabric softener and deodorizer is used, and increase income for Family Welfare Empowerment Members in Kangkung Village, Mranggen Subdistrict, Demak Regency, if the softeners and perfumers of the clothes are marketed. The results of this training are fabric softeners and deodorizers with a pH of 5, this is in accordance with the Indonesian National Standard (SNI) 16-0218-1997.